2016
DOI: 10.5123/s1679-49742016000200016
|View full text |Cite
|
Sign up to set email alerts
|

Avanços do Plano de Ações Estratégicas para o Enfrentamento das Doenças Crônicas não Transmissíveis no Brasil, 2011-2015

Abstract: we found progress regarding surveillance, health promotion and comprehensive care; in general, the goals of the Plan are being met.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
17

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 2 publications
0
21
0
17
Order By: Relevance
“…The study confirmed previous estimates that indicated that salt intake in Brazil was high compared not only with the WHO recommendation (5 g/day) but also with other countries 5,9,13,15 . Given the association of high salt intake with AH 10 and CVDs 14 , the data presented reinforce the need to implement preventive actions aimed at reducing its consumption and the events related to chronic NCDs [39][40][41] .…”
Section: Discussionmentioning
confidence: 95%
“…The study confirmed previous estimates that indicated that salt intake in Brazil was high compared not only with the WHO recommendation (5 g/day) but also with other countries 5,9,13,15 . Given the association of high salt intake with AH 10 and CVDs 14 , the data presented reinforce the need to implement preventive actions aimed at reducing its consumption and the events related to chronic NCDs [39][40][41] .…”
Section: Discussionmentioning
confidence: 95%
“…4 Integrality needs to be advanced to mobilize and make addressing the CNTDs a cross-cutting theme in the process of organizing services and health in general. 66 The center of strengthening community action is the more empowerment of the communities. The promotion works through concrete and effective community actions in the development of priorities, decision making, strategy definition and implementation, in order to improve health conditions.…”
Section: /18mentioning
confidence: 99%
“…Consultations performed in community practice are considered an essential element in health care for people with CNTDs, provided that they are carried out individually and participatively, providing conditions for improving people's quality of life and, consequently, their health situation. 66 Regarding activities of collective scope, they are characterized by groups. These are spaces in which health promotion actions can take place, since there is the possibility of providing broadening of the individual's understanding of their health/disease process, and thus favoring changes in lifestyle habits.…”
Section: /18mentioning
confidence: 99%
See 1 more Smart Citation
“…O aumento da expectativa de vida da população brasileira, a melhoria significativa das condições sanitárias e o acesso aos benefícios advindos do conhecimento científico e tecnológico geraram mudanças no perfil de morbimortalidade, levando à situação atual de prevalência das doenças crônicas não transmissíveis (DCNTs), além de possibilitar o tratamento de enfermidades que até então evoluíam rapidamente ao óbito. Esses agravos à saúde são caracterizados por terem etiologia múltipla e curso prolongado, resultando em incapacidade funcional (Carvalho, Oliveira, Santos, Andrade, & Silva, 2016;Santana, 2012). Apesar da incurabilidade, parte dessas condições pode ser tratada e ter seus sintomas controlados.…”
Section: Introductionunclassified